2023
DOI: 10.1093/icvts/ivad010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intraoperative haemoadsorption therapy on cardiac surgery for active infective endocarditis with confirmedStaphylococcus aureusbacteraemia

Abstract: Objectives Sepsis caused by infective endocarditis, due to staphylococcus aureus is associated with significant morbidity and mortality. Blood purification using hemoadsorption may attenuate the inflammatory response. We investigated the effect of intraoperative hemoadsorption on postoperative outcomes in staphylococcus aureus infective endocarditis. Methods Patients with confirmed staphylococcus aureus infective endocarditis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…Notwithstanding, based on the results of studies presented here, it seems that hemoadsorption may improve outcomes in high-risk IE patients (5,7,9,11,12,45). This is supported by the high baseline risk scores (EuroSCORE-II > 8%) (51) in the studies that reported benefit with hemoadsorption.…”
Section: Infective Endocarditissupporting
confidence: 63%
“…Notwithstanding, based on the results of studies presented here, it seems that hemoadsorption may improve outcomes in high-risk IE patients (5,7,9,11,12,45). This is supported by the high baseline risk scores (EuroSCORE-II > 8%) (51) in the studies that reported benefit with hemoadsorption.…”
Section: Infective Endocarditissupporting
confidence: 63%
“…The benefit of non-selective depletion of cytokines has not yet been proven in this population of patients. Notwithstanding, based on the results of studies presented here, it seems that hemoadsorption may improve outcomes in high-risk IE patients [ 5 , 6 , 11 14 ]. This is supported by the high baseline risk scores (EuroSCORE-II > 8%) [ 51 ] in the studies that reported benefit with hemoadsorption.…”
Section: Discussionmentioning
confidence: 81%
“…The most frequently reported outcome was vasopressor requirements, and in all but two studies [ 10 , 13 ], a significant reduction (where statistical analysis was performed) in vasopressor drug demand was observed with intraoperative hemoadsorption. Cytokine reductions with CytoSorb ® were confirmed in two studies [ 5 , 10 ], while significantly lower postoperative sepsis-related mortality with hemoadsorption was observed in four studies [ 7 , 11 , 13 , 14 ]. Out of these four, one recent study showed a significantly reduced 30- and 90-day mortality in selected patients suffering from Staphylococcus aureus -derived infective endocarditis [ 14 ].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations